Multifunctional Lignin-Based Composite Materials for Emerging Applications - Ma, Chang; Kim, Tae-Hee; Liu, Kun; Ma, Ming-Guo; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
Lignin, the second most abundant plant-derived biopolymer, exhibited numerous advantages such as plentiful functional groups, good biocompatibility, low toxicity, and high carbon content, which can be transformed into composites, derivatives, and chemicals, as well as lignin-derived carbon materials. In this review article, the properties and categories of lignin are introduced in briefly, and the latest progress of lignin-based composites and lignin-derived carbon materials is summarized. Finally, the current challenges and future developments were suggested based on our knowledge. It is expected that this review paper favored the applications of composites and lignin-derived carbon materials in the future.